1993
DOI: 10.1111/j.1748-1716.1993.tb09519.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic baroreflex control of vascular resistance in comfortably warm man. Analyses of neurogenic constrictor responses in the resting forearm and in its separate skeletal muscle and skin tissue compartments

Abstract: Resting forearm vascular resistance changes elicited in male volunteers by graded reflex sympathetic activation evoked by graded lower body negative pressure (LBNP) were studied at room temperatures of 24-25 and 20-21 degrees C. The latter condition caused strong suppression of skin flow and permitted preferential analysis of muscle responses and, by comparison with responses at 24-25 degrees C, secondary estimation of circulatory reactions in the skin. Short-lasting LBNP-bouts (1.5 min) allowed analyses of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…On the other hand, in humans the concept that arterial baroreceptors have only a minor influence on limb vascular resistance was developed (17,18). In contrast to these data, Edfeldt and colleagues have demonstrated in their studies using lower body negative pressure that deactivation of the arterial baroreceptors significantly contributes to the regulation of forearm resistance, which involves active participation of the skin microvasculature (19–21). In a recent study, Bernardi and colleagues reported that laser Doppler flowmetry fluctuations were responsive to sinusoidal neck suction, indicating a response to sympathetic modulation.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, in humans the concept that arterial baroreceptors have only a minor influence on limb vascular resistance was developed (17,18). In contrast to these data, Edfeldt and colleagues have demonstrated in their studies using lower body negative pressure that deactivation of the arterial baroreceptors significantly contributes to the regulation of forearm resistance, which involves active participation of the skin microvasculature (19–21). In a recent study, Bernardi and colleagues reported that laser Doppler flowmetry fluctuations were responsive to sinusoidal neck suction, indicating a response to sympathetic modulation.…”
Section: Discussionmentioning
confidence: 92%
“…However, physiological experiments in healthy humans give hint that vessels of the glabrous skin of the fingers are not under cholinergic control. 10 Reduced activity in central noradrenergic neurons and peripheral synaptosomal reuptake of norepinephrine are responsible for termination of VRs of the vessels of the fingers. Sustained activation of central and/ or peripheral sympathetic neurons may account for the observed prolongation of VR observed by us after subchronic administration of venlafaxine.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence the TNZ in supine position is shifted upward relative to the TNZ in upright position. Furthermore, arterial baroreceptor reflexes that accompany a supine position cause vasodilatation both in muscle and skin tissue (+57% blood flow in femoral artery), which decreases insulation and contributes to the upward shift of the TNZ in supine vs. upright position (84).…”
Section: Energy Expenditurementioning
confidence: 99%